ANALISIS STRATEGI MANAJEMEN ZAKAT PADA BAZNAS KABUPATEN BONDOWOSO DAN JEMBER - Hamim (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Data from the Strategic Study Center of the Badan Amil Zakat Nasional (BAZNAS) Institutional Index Rating in East Java indicates that Bondowoso Regency has a score of 0.42 (fairly good) and Jember has a score of 0.45 (fairly good). In terms of ranking, Bondowoso and Jember are ranked 21st and 20th out of 23 regencies/cities, respectively. This presents a challenge for these two regencies, considering the Zakat index with institutional indicators (collection, management, distribution, and reporting) is very low and almost approaches the Poor Zakat index (0.21-0.40). This research employs a descriptive qualitative research method and data collection techniques in the form of observation, interviews, and documentation. The findings of this research are: 1) The management of zakat at BAZNAS has been effective and in accordance with Law Number 23 of 2011 & BAZNAS RI Regulation Number 1 of 2023. 2) The supporting and inhibiting factors in BAZNAS can be well collaborated, so that according to SWOT analysis, these two BAZNAS are in a strategy of supporting aggressive growth policies.